1991
DOI: 10.1590/s0071-12761991000100014
|View full text |Cite
|
Sign up to set email alerts
|

Acumulação de matéria seca, absorção de N, P e K pelo cafeeiro (Coffea arabica L. cv. Catuaí) com dois, tres, quatro e cinco anos de idade, nas fases fenológicas de repouso, granação e maturação vegetando em um latossolo vermelho amarelo, fase cerrado

Abstract: Em uma plantação de cafeeiro (Coffea arabica L. cv. Catuaí) com dois, três, quatro e cinco anos de idade no campo, situada em Latossolo Vermelho Amarelo, fase cerrado, na Fazenda Santo Izidro, município de Salto, SP. , determinou-se a acumulação de matéria seca e absorção de N, P e K no caule, ramos, folhas e frutos, durante as fases fenológicas de repouso, granação e maturação. Concluiu-se que: - Constitui exceção o potássio que mostra os valores mais elevados aos cinco anos, para as três épocas; - A maior ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These results suggest that the most exported nutrient by the beans is N and the requirements for N and K to obtain good yields are equivalent. Cietto & Haag (1995) found N:K ratios of 1.41 and 1.12 for 3-and 5-year-old coffee plants, respectively, and concluded that the requirement for N is greater than that for K. Neves et al (2006) found mean N:K ratios in leaves of 2.36 and 1.51 at 31 and 55 months of cultivation, respectively, concluding that the requirement for N is greater than that for K to obtain good yield, although the greatest proportion of K was found in coffee beans, and of N in leaves. Silva (1999) stated that the requirements of coffee for K are equivalent to those for N.…”
Section: Chemical Composition Of Leaves and Beansmentioning
confidence: 99%
“…These results suggest that the most exported nutrient by the beans is N and the requirements for N and K to obtain good yields are equivalent. Cietto & Haag (1995) found N:K ratios of 1.41 and 1.12 for 3-and 5-year-old coffee plants, respectively, and concluded that the requirement for N is greater than that for K. Neves et al (2006) found mean N:K ratios in leaves of 2.36 and 1.51 at 31 and 55 months of cultivation, respectively, concluding that the requirement for N is greater than that for K to obtain good yield, although the greatest proportion of K was found in coffee beans, and of N in leaves. Silva (1999) stated that the requirements of coffee for K are equivalent to those for N.…”
Section: Chemical Composition Of Leaves and Beansmentioning
confidence: 99%